Analysis of solubility, absorption heat and kinetics of CO2 absorption into 1-(2-hydroxyethyl)pyrrolidine solvent. (27th April 2017) - Liu, Helei; Li, Moxia; Idem, Raphael; (PT) Tontiwachwuthikul, Paitoon; Liang, Zhiwu
Highlights: Reaction kinetics of 1-(2-HE)PRLD with CO2 is presented using stopped-flow technology. CO2 absorption heat of 1-(2-HE)PRLD is shown. The plot of the kinetics versus heat absorption is created. Abstract: The CO2 absorption performance of aqueous 1-(2-hydroxyethyl)pyrrolidine (1-(2-HE)PRLD) was studied with respect to kinetics (i.e., in terms of the pseudo-first-order rate constant ( k o ) and second-order reaction rate constant ( k 2 ), obtained using the stopped-flow apparatus). CO2 equilibrium solubility and heat of CO2 absorption were evaluated at the temperature range of 293–313 K in the 1-(2-HE)PRLD concentration range of 0.20–1.00 mol/L for kinetics and at 2 M for CO2 solubility. The values of k o were then represented using the base-catalyzed hydration mechanism, which gave an acceptable AAD of 10%. In addition, Brønsted plots of k 2 vs. pKa were developed to predict k 2 using pKa values of various tertiary amines. In addition, the CO2 equilibrium solubility and CO2 absorption heat were obtained in this work. Based on a comparison with other amines such as MEA, MDEA and 1DMA2P, 1-(2-HE)PRLD showed better performance in terms of CO2 equilibrium solubility (DEAB > 1-(2-HE)PRLD > 1-(2HE)PP > 1DMA2P > MDEA > MEA > DEA), kinetics (MEA > DEA > DEAB > 1-(2-HE)PRLD > 1-(2-HE)PP > DMMEA > 1DMA2P > MDEA.) and CO2 absorption heat (MEA > DEA > MDEA > DEAB > 1-(2-HE)PRLD > 1-(2HE)PP > 1DMA2P). Therefore, 1-(2-HE)PRLD could be considered as a good alternative solvent for CO2 capture. A correlation between kinetics and heat of CO2 absorption has been developed to guide the design of what can be considered to be ideal amine solvents for CO2 capture.